“And I have no face, I have wanted to efface myself” Sylvia Plath’s Autothanatography or Death Writing - Nicolas Pierre BOILEAU (E-REA)
Plath’s work has often been described as an auto/biographical account of her death wish, and for some, her 1963 suicide was the evidence confirming her obsession for the morbid. The overwhelming presence of grief and mourning in her life has also been said to adumbrate the tone of most of her poems. Yet, very little has been done on the question of “autothanatography,” even if indeed Plath’s works seem to be far more concerned about death than life. Autothanatography suggests that there is a form of autobiographical writing that is less interested in the author’s past life than in the future/ upcoming death of the subject. Following in the footsteps of French psychoanalytical theory on Melancholia, this paper seeks to observe one of the blind spots of Plath’s critical literature, that is the real presence of death in language, causing subjects to be impossible to grasp and locate. Plath’s autobiographical writings were not means to fight off death, but to account for its looming presence in her writing as well as in her life. Thereby, Plath’s responsibility regarding her obsessional writing of death will be toned down, and the poems will be shown to bear the stigmas of the linguistic death that Plath reveals.